Hubungan Antara Kebiasaan Olahraga, Obesitas Dan Stres Dengan Kejadian Hipertensi Pada Remaja Di Sma Negeri 10 Semarang - Arum Tri Wijayanti; Sri Noor Mintarsih; Mohammad Jaelani (JURNAL RISET GIZI, 2016)
Background: Hypertension is a disorder of the cardiovascular system, it’s still a burden on public health because of its prevalence is high. Factors that cause hypertension such as lack of physical activity, obesity and stress state. The prevalence of teenagers hypertension in the age group 15-24 years are 8,7%.Objective: To identify the correlations between exercise habits, obesity and stress with hypertension in adolescents in Senior High School 10 Semarang.Methods: The study of public nutrition with case control approach (matching sex) with each sample case and control groups of 37 students. Collecting data include measurement of blood pressure, exercise habits, height and weight measurements and stress. To determine the relationship between variables used Mc Nemar test with α = 95%.Results: The average systolic blood pressure / diastolic in hypertension group was 131.70 / 74.61 mmHg and the group does not hypertensive 103.08 / 59.41 mmHg. 86.5% of adolescents with hypertension lack of exercise, while adolescents are not hypertensive 83.8% less exercise. Adolescents with hypertension 62.6% are obese, while adolescents are not hypertensive only 8.1%. Most (89.2%) adolescents both hypertensive and non-hypertensive do not experience stress. Results of bivariate analysis is not significant correlations between exercise habits with hypertension (p = 1.000), there is a correlations between obesity and hypertension (p = 0.001, OR = 8) and there is not significant correlations between stress and hypertension (p = 1.000).Conclusions: Obesity is correlated with hypertension. While exercise habits and stress are not correlated. Suggested adolescents maintain a healthy weight.